A BASIC STUDY ON RIDE COMFORT EVALUATION BASED ON BIOSIGNALS - Yiming, Alimujiang; ISHIDA, Tateki; KAWAMURA, Akira; TOMIYAMA, Kazuya (JOURNAL OF PAVEMENT ENGINEERING, JSCE, 2007)
In this research, biosignals, heart rate and skin conductance response, were discussed as indices for the evaluation of ride comfort. A driving simulator that reproduces the behavior of vehicles traveling on uneven road surfaces was used for subjective evaluation of the road profile. At the same time, the fluctuations in the heart rate and skin conductance response were measured. From the results, it was found that the test subject's heart rate increased when driving on the uneven roads, and as the vertical acceleration R.M.S. value increased, the variability of heart rate increased. Moreover, it was also confirmed that the test subject's skin conductance response increased when driving on the uneven roads, but there was no significant relations between the vertical acceleration R.M.S. value and variability of skin conductance response.